The Effect of Corporate Social Responsibility and Cash Holding on Firm Value in Manufacturing Companies in the Industrial Sector Listed on the Indonesia Stock Exchange in 2020–2024 - Almeidina, Dhea; Margareth, Sarah; Yusuf, Maulana; Maulana, Dadang; Yanti, Febri; Yustiani, Paras; Mahwiyah, Mahwiyah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the effect of Corporate Social Responsibility and Cash Holding on the value of companies listed on the Indonesia Stock Exchange. Utilizing secondary time series data spanning from 2020 to 2024, the research investigates how each variable, both individually and collectively, influences firm value. The findings indicate that Corporate Social Responsibility has a positive and significant impact on company value, supported by a probability value below the standard significance level. Similarly, Cash Holding shows a positive and significant effect on firm value, suggesting that companies with higher liquidity are perceived more favorably by investors. Moreover, the joint analysis of both variables demonstrates a significant combined influence on firm value, reinforcing the notion that corporate responsibility and effective cash management play crucial roles in enhancing market perception and investor confidence.